RELATIONSHIP OF ATTITUDE TOWARDS ENTREPRENEURSHIP TO ENTREPRENEURIAL INTENTION THROUGH ENTREPRENEURSHIP EDUCATION (CASE STUDY OF HIGH SCHOOL STUDENTS IN SURABAYA) - Santho Vlennery Mettan; Veronika Rahmawati (Research In Management and Accounting (RIMA), 2024)
The nation's progress can be measured by the number of students who are educated to a high level and understand the importance of entrepreneurship. This approach aligns with the Government's development plan and can be realized with the support of students who venture into entrepreneurship. High school students are fully capable of becoming entrepreneurs since they are the future drivers of the economy. The Government provides support through the National Entrepreneurship Movement (GKN) Program, which is implemented cohesively by all ministries, led by the Coordinating Ministry for Economic Affairs. The Ministry of National Education is one of the participating ministries in the program. This study investigates the factors influencing high school students' entrepreneurial intention regarding attitudes towards entrepreneurship by analyzing the impact of entrepreneurial education in Surabaya. The technique used is multiple regression analysis using the mediator variable, using a questionnaire distributed to high school students in Surabaya with 153 participants. The results showed that out of the 4 hypotheses, 2 hypotheses have been accepted, and 2 hypotheses have been rejected. For the hypothesized mediation relationship does not occur. Therefore, the relationship is a direct relationship between the attitude toward entrepreneurship and entrepreneurial intention. The follow-up research plan will include new variables and more diverse subjects. JEL Class: M200, M21, L26